Influence of the Novel Anticancer Agents on the Activity of Outward Rectifier Potassium Currents in Human Prostate Cancer Cell Line - LNCaP - Malathi, R. (Asian Journal of Pharmaceutics (AJP), 2017)
Background: Phenolic compounds are ubiquitous in dietary fruits and vegetables and have been proposed to have antioxidant, antibacterial, anti-inflammatory, and anticancer effects. Voltage gated K+ channels (IK) contribute to various cellular mechanisms involved in the tumor cell progression. Therefore, the modulation of IK current may be a potential target for cancer therapy. In this study, we electrophysiologically characterized four phenolic compounds for their modulatory activities on IK currents. Materials and Methods: The whole cell configuration of the patch clamp recording technique was used to record the IK currents from human prostate cancer line (LNCaP). In addition, 200 Î¼M of phenolic compounds (curcumin, resveratrol, rutin, and troxerutin) were externally perfused to the cells. Results: Obtained results provide evidence that resveratrol at 200 Î¼M inhibited more than half of the IK current amplitude. On the other hand, curcumin, rutin, and troxerutin did not show any modulatory effect on IK current in LNCaP cells. Conclusion: This study demonstrates that not all the anticancer compounds are effective inhibitors of IK current, but only few of them. The IK current inhibitors might exhibit effective antimetastatic properties.